2020
DOI: 10.3389/fvets.2020.00423
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Pimobendan and Its Metabolite O-Desmethyl-Pimobendan Following Rectal Administration to Healthy Dogs

Abstract: This study describes the pharmacokinetics of parent pimobendan (PIM) and its active metabolite, o-desmethyl-pimobendan (ODMP), after oral and rectal administration of pimobendan to healthy dogs. Animals: A total of eight healthy privately owned dogs were used in this study. Procedures: The dogs received a single dose (0.5 mg/kg) of a commercially available pimobendan tablet per os (PO). Twelve blood samples were collected over a 12-h period for pharmacokinetic analysis. After a 24-h washout period, the dogs re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In the current study, pimobendan was given by injection; therefore, the C max of ODMP is 3.4 times higher while the T max is 5.6 times faster than those of the previous study. In addition, the half-life of pimobendan and ODMP in this study was shorter while the AUC was presumably the same level based on data provided in the previous study ( 37 ).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the current study, pimobendan was given by injection; therefore, the C max of ODMP is 3.4 times higher while the T max is 5.6 times faster than those of the previous study. In addition, the half-life of pimobendan and ODMP in this study was shorter while the AUC was presumably the same level based on data provided in the previous study ( 37 ).…”
Section: Discussionsupporting
confidence: 76%
“…In this study, the injectable pimobendan provides immediately positive inotropic effect which is suitable for dogs presenting with acute CHF. Previous study in healthy dogs demonstrated that the rectal administration of pimobendan at a dose of 0.5 mg/kg provides rapid absorption and achieves therapeutic plasma concentration which may be suitable for dog with CHF ( 37 ). In that study, the T max and C max of ODMP were 1.7 ± 1.1 h and 8.8 ± 4.8 ng/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due mainly to the differences in the dosages given to the dogs. It is also known that differences in the design of experiments (e.g., analytical method, dosage, and age of subjects) or the effects of different formulations may lead to such discrepancies [ 19 ]. Although the C max values in the different studies are different, the clearance of pimobendan in the current study is similar to previous reports [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, pimobendan is rapidly metabolized in the liver to the more potent metabolite UDCG 212. 24,46,47 Investigating only the effect of pimobendan in our study may not accurately reflect the substances to which canine platelets in vivo are exposed. Therefore, investigating the effect of UDCG 212 on platelet aggregation using a mixture of pimobendan and UDCG 212 or, perhaps even more relevant, blood from dogs treated with pimobendan would be relevant and could likely result in different findings than reported in our study.…”
Section: Association Between Basal Platelet Aggregation Response and ...mentioning
confidence: 94%